Rancang Sistem Informasi Aplikasi Praktikum Simulasi Perbankan - Sidik, Muhamad; Mahesti, Triloka; Z A, In’am Fanany (MEANS (Media Informasi Analisa dan Sistem), 2024)
Currently, the learning process in the field of banking predominantly relies on approaches, focusing on the delivery of theoretical concepts with minimal practical application through personal computer use. As a result, students lack real-world experience related to the operational aspects of banking systems as they occur in the workplace. Therefore, this study aims to design a banking system that integrates various key components of banking activities, with adjustments according to the specific functions of each component